The Effect of Dino Animation Videos on Fourth Grade Students’ Vocabulary Achievement at SDN 006 Sungai Kunjang - Elok Prihatina; Hasby Sjamsir; Weningtyas Parama Iswari (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2019)
This study aimed to find out 1) the vocabulary achievement of fourth grade students at SDN 006 Sungai Kunjang who are taught with using Dino animation videos, 2) the vocabulary achievement of fourth grade students at SDN 006 Sungai Kunjang who are taught without using Dino animation videos, and 3) whether there is any significant difference in the fourth grade students’ vocabulary achievement who are taught with and without using Dino animation videos. This study was quantitative research, which was classified as quasi- experimental research. This study used non- random sampling/ purposive and non- equivalent control group design, where the most common quasi experimental research is the comparison between (pre- test and post - test ) group control and group experimental design. The population of this study was the students at SDN 006 Sungai Kunjang, Samarinda. The total number of participants were 76 students from two classes (4B and 4C). The mean score of the experimental group was 58.3 (low) on Pre- test and 77.1(high) on Post - test and for control group was obtained 55.6 (low) on Pre- test and 65.4(average) on Post - test. After being analyzed both mean scores by using SPSS, it was found that the significance value of the difference between the two mean scores was 0.002 <α 0.05. The computation showed that the mean scores of the two groups significantly differed. In conclusion, the alternative hypothesis (Ha) is accepted and Null hypothesis (H0) is rejected. Based on the result of Paired T- test, alternative hypothesis (Ha) was accepted, thus resulted a significant effect